The Influence of Product Quality, Brand Image and Electronic Word of Mouth on Interest in Buying Ms Glow Body Lotion on Shopee Ecommerce for National University Students - Arsanti Padila; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of the independent variables in this study in the form of product quality variables, brand image variables and electronic word of mouth variables on the dependent variable of this study changing interest in buying Body lotion Ms glow. The method in this study is descriptive - quantitative with a population of respondents or more specifically consumers of Ms. Glow's body lotion. The sample which is the research respondent is 96 with non-probability sampling technique. In using the non-probability sampling technique, it is expected that the sample is in accordance with the terms or criteria needed in this study. The data used is in the form of primary data by distributing questionnaires with the model test in the form of multiple linear regression processed using SPSS 23. The results were found after being analyzed using data processing with the following conclusions that product quality, brand image and electronic word of mouth have a positive and significant effect on buying interest. Previously tested against statement items which were declared valid and reliable